Kajian Kepustakaan : Pengaruh Latihan Circuit untuk Meningkatkan Passing Bawah Permainan Bola Voli - Atmaranu, Atmaranu; Jariono, Gatot; Fatoni, Muhad (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to analyze the effects of circuit training on improving underhand passing in volleyball through a literature review. Underhand passing is a fundamental technique in volleyball, used to receive serves and opponent attacks. Circuit training combines structured physical and technical exercises with minimal rest, aiming to enhance players' skills and physical fitness. The results show that circuit training significantly improves underhand passing abilities in terms of accuracy, consistency, and speed. Additionally, this training increases muscle strength, balance, and endurance, which are crucial for supporting overall game performance. Conclusion, circuit training is effective in developing underhand passing skills in volleyball players. Keywords: Basic Technique, Circuit Training, Physical Fitness, Underhand Passing, Volleyball